Agricultural Land Lease in Slovakia – selected issues and economic aspects - Lazíková, Jarmila; Tarišková, Barbora (Ekonomia i Prawo. Economics and Law, 2025)
Motivation: Agricultural land is an important natural resource and a fundamental factor of production that Slovak farmers typically use based on numerous land lease contracts concluded with landowners, due to the high fragmentation of land ownership in Slovakia. Therefore, the legal regulation of agricultural land lease is crucial for the development of the agricultural land market, and it is essential to properly establish the legal rules that market participants should follow. Aim: The main objective of our article is to determine whether the selected legal norms regulating land lease (the minimum rent and the administrative rent, and its modifications.), are appropriately adapted to the conditions of the land lease market in Slovakia. Results: The results of the study indicate a need for legislative amendments if these legal rules are to fulfil the purpose intended by the legislator, rather than merely representing an unnecessary element within the already complex framework of land-related legal regulations in Slovakia. Moreover, we formulated de lege ferenda recommendations based on an analysis of land rents in selected agricultural regions of Slovakia.